OPTIMIZATION OF WASTE MANAGEMENT LAND IN CREATING LOCAL FOOD SECURITY AND A HEALTHY ENVIRONMENT IN KUNINGAN REGENCY - Nurdin, Nurdin; Agus Yadi Ismail; Iing Nasihin; Ika Karyaningsih; Ilham Adhya; Nina Herlina; Wina Waniatri; Fina Nadia Silma; Muhamad Rijal; Ossa Yuniar Pupatriyani (Universitas PGRI Yogyakarta, 2025)
The Jati Tengah integrated waste management site consists of a waste processing building and land designated for the development of waste processing products through the concept of reduce, reuse and recycle. The concept that has not been implemented requires community participation to optimize the land. This community empowerment activity aims to increase community participation in optimizing the land by planting local plants as an effort to increase food security. Participatory Rural Appraisal is the right method to increase community involvement. Empowerment activities include educational activities for the community through discussion groups that discuss the theme of land optimization. The next activity is planting peanuts, mangoes, avocados, durians, guavas, coconuts, bay trees and teak trees with an intercropping system. Planting begins with land preparation, digging planting holes and providing compost, planting and harvesting. Peanuts are harvested first, then cassava. The community is more interested in planting types of nuts because they adapt to weather conditions. The next service priority is to plant various types of nuts by maintaining an intercropping system. Keywords: waste, land, food, participation, service